2008
DOI: 10.1016/j.msea.2007.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Structure and property evaluation of a vacuum plasma sprayed nanostructured tungsten–hafnium carbide bulk composite

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. AbstractVacuum plasma spray (VPS) forming of tungsten-based metal matrix nanocomposites (MMCs) has shown to be a cost effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Recently, researches on fabrication tungsten or tungsten-based parts by PSF have been reported by Wu et al, 9) Rea et al, 10) Hovis et al, 6) Mutasim et al…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researches on fabrication tungsten or tungsten-based parts by PSF have been reported by Wu et al, 9) Rea et al, 10) Hovis et al, 6) Mutasim et al…”
Section: )mentioning
confidence: 99%
“…Rea et al 10) explored and characterized vacuum plasma spray formed tungsten parts reinforced by nanoscale HfC particles. In addition, a blend of W, nickel (Ni) and iron (Fe) powders was plasma sprayed onto a mandrel of desired configuration, as described by Hovis et al 6) They claimed that the formation of thin-walled structure made by plasma spraying can significantly reduce shrinkage and prevent cracks while enhance physical properties comparing those obtainable by PM method.…”
Section: )mentioning
confidence: 99%
“…The functional structure which attaching these refractory materials on the surface of ceramic or carbon/carbon composite can have substantial advantages of high performance, cost effectiveness and light weight. [3][4][5] Requirements for these combined ceramic or carbon/carbon composite are endurance under high temperature and the chemical stability with the refractory material. At room temperature, lots of promising refractory materials such as W, Re, and W-Re alloy do not form carbides with ceramic or carbon/carbon composite but under the high temperature, W and Re can form a solid solution with carbon.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) Almost any feedstock can be sprayed onto the mandrel in a controllable manner to provide a compact of desired shape and wall thickness with benefits of simplifying fabrication process and cost reduction. Recently, researches on fabrication refractory metallic tungsten (W) or W-based products by PSF have been reported by Wu et al 10) and Rea et al 11) The former 10) presented the technique of PSF method to make large-scale W tubular heating elements, while the latter 11) explored and characterized vacuum plasma spray formed W alloy parts reinforced by nanoscale HfC particles. In addition, Chwa et al 12) reported that Mo-Cu composites fabricated by vacuum plasma spraying.…”
Section: Introductionmentioning
confidence: 99%
“…13) In order to reduce these defects, applying HIPing to further densify the deposits (including ceramics, intermetallics and high-temperature metallic alloys) has been reported by several groups. 10,11,14,15) Those early works showed that HIPing played great influence on microstructure changes and physical properties of plasma sprayed deposits. However, to our knowledge, there is no work on the relation between microstructure and mechanical property of PSF Mo parts before and after HIPing treatment.…”
Section: Introductionmentioning
confidence: 99%